THE QUESTION OF THE OBSERVANCE OF THE INTERESTS OF COASTAL STATES IN DETERMINING THE LEGAL REGIME OF THE REGIONAL SEAS (FOR EXAMPLE, BLACK SEA) (Journal of actual problems of jurisprudence, 2019)
This article is devoted to the issue of respect for the interests of coastal states in determining the legal regime of the regionalseas. In particular, the author shows specificity of the legal regime of the regional seas by the example of Black Sea, makesconclusions about the need to resolve the status of such seas exclusively by the coastal states, considering a number of universallyaccepted treaty and customary norms of international maritime law.